2021
DOI: 10.1002/nau.24733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of transcutaneous tibial nerve stimulation or pelvic floor muscle training on sexual dysfunction in female multiple sclerosis patients reporting overactive bladder

Abstract: Aims: Sexual dysfunction (SD) is common in female patients with multiple sclerosis (MS) reporting overactive bladder (OAB) symptoms. The aim of the study was to evaluate the effects of transcutaneous tibial nerve stimulation (TTNS) and pelvic floor muscle training (PFMT) with biofeedback on SD in female patients with MS reporting OAB symptoms. Methods: Patients with overactive bladder and SD were allocated to receive TTNS or PFMT daily. Overactive bladder symptoms, sexual functions, and sexual quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…When people do exercises under a physiotherapist's supervision, their commitment to exercise tends to increase. As stated in the previous studies conducted in people with multiple sclerosis, 27,29,30 we also did not observe any side effects or adverse events related to PFMT. The evidence for the feasibility and effects of Tele-PFMT is limited.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When people do exercises under a physiotherapist's supervision, their commitment to exercise tends to increase. As stated in the previous studies conducted in people with multiple sclerosis, 27,29,30 we also did not observe any side effects or adverse events related to PFMT. The evidence for the feasibility and effects of Tele-PFMT is limited.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study reported significant improvements in arousal, desire, and lubrication subdomains of sexual function after an 8-week PFMT 39. Another study in people with multiple sclerosis also showed improvements in sexual function after PFMT with electromyography biofeedback and/or electrical stimulation 29. The primary outcome measure in these studies was sexual dysfunction, only female participants were included, and a female-specific assessment tool was used to assess sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies investigated PFMT alone, with or without physiotherapist guidance [ 46 ], or PFMT in addition to other devices or methods, such as intravaginal neuromuscular electrical stimulation (NMES), electromyographic (EMG) biofeedback [ 49 , 50 ], transcutaneous tibial nerve stimulation (TTNS) [ 47 , 49 , 54 , 55 ].…”
Section: Pelvic Floor Rehabilitation In Msmentioning
confidence: 99%
“…Although with different study protocols, PFMT presents several advantages: it is associated with improvements in LUTS severity [ 45 , 46 , 47 , 48 ], QoL [ 45 , 46 , 52 ], level of anxiety and depression [ 52 ], and sexual dysfunctions [ 54 , 55 , 56 ].…”
Section: Pelvic Floor Rehabilitation In Msmentioning
confidence: 99%
“…The literature shows improvements in SD in women through the application of genital vibration [14,15] or transcutaneous tibial nerve stimulation (TTNS) [16,17]. With respect to transcutaneous peripheral neuromodulation through the tibial nerve (L4-S3) [18], this presents an area of easy access to such nerve, which shares the same metameric area with the somatic and parasympathetic innervation of the pelvic floor (S2-S4) [19].…”
Section: Introductionmentioning
confidence: 99%